The influence of culture on perceived ethical problems and ethical judgements / Maheran Zakaria - Zakaria, Maheran (University Publication Centre (UPENA), 2011)
The objective of this study is to examine the influence of culture on perceiving problems which in turn influence ethical judgments. 4 total of 880 questionnaires were distributed to business students in public institutions of higher learning in Malaysia and approximately 550 questionnaires were returned. However: only 524 were usable. Data were analyzed using SPSS 16.0. From the results, it can be concluded that culture is strongly associated to perceived ethical problems and ethical judgments. Perceived ethical problems are also strongly related to ethical judgments. In addition, the hierarchical multiple regression results indicate that perceived ethical problems mediate the relationship between culture and ethical judgments. Hence. understanding the culture values provide better insight in enhancing ethical judgments.